Lithuanian Publisher’s Needs for Training (Libellarium: journal for research in the field of information and related sciences, 2016)
The survey on the training and professional development needs of Lithuanian publishers was designed and conducted. The pilot research showed that publishers in Lithuania have an interest in professional training. According to the results, the need for training among the employees of Lithuanian publishing houses depends on the previous training experience: the more training courses the employee had before, the greater need for training he/she expresses. 82% of publishing house employees from four different fields agreed and strongly agreed on the need for training. Very few employees would like to pay for training by themselves. The identified need for training appears to reflect the nature of the problems encountered in the publishing field in Lithuania: Copyright, Law & Rights is the most wanted training topic among managing directors. The list of preferred topics for training can be used as the grounds for creating a supply of publishing training courses.
Keywords: needs for training; publishers; Lithuania